305dre
Answered

Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Select the correct answer.

Which point lies on the circle represented by the equation [tex](x-3)^2+(y+4)^2=6^2[/tex]?

A. [tex](9, -2)[/tex]
B. [tex](0, 11)[/tex]
C. [tex](3, 10)[/tex]
D. [tex](-9, 4)[/tex]
E. [tex](-3, -4)[/tex]


Sagot :

Let's analyze the given options to determine which point lies on the circle defined by the equation [tex]\((x-3)^2 + (y+4)^2 = 6^2\)[/tex].

First, we note that the center of the circle is [tex]\((3, -4)\)[/tex] and its radius is [tex]\(6\)[/tex].

We need to check each given point to see if it satisfies the circle's equation.

Option A: [tex]\((9, -2)\)[/tex]

Substitute [tex]\(x = 9\)[/tex] and [tex]\(y = -2\)[/tex] into the equation:
[tex]\[ (9-3)^2 + (-2+4)^2 = 6^2 \][/tex]
[tex]\[ 6^2 + 2^2 = 36 \][/tex]
[tex]\[ 36 + 4 = 40 \neq 36 \][/tex]
So, [tex]\((9, -2)\)[/tex] does not lie on the circle.

Option B: [tex]\((0, 11)\)[/tex]

Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = 11\)[/tex] into the equation:
[tex]\[ (0-3)^2 + (11+4)^2 = 6^2 \][/tex]
[tex]\[ (-3)^2 + 15^2 = 36 \][/tex]
[tex]\[ 9 + 225 = 234 \neq 36 \][/tex]
So, [tex]\((0, 11)\)[/tex] does not lie on the circle.

Option C: [tex]\((3, 10)\)[/tex]

Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = 10\)[/tex] into the equation:
[tex]\[ (3-3)^2 + (10+4)^2 = 6^2 \][/tex]
[tex]\[ 0^2 + 14^2 = 36 \][/tex]
[tex]\[ 0 + 196 = 196 \neq 36 \][/tex]
So, [tex]\((3, 10)\)[/tex] does not lie on the circle.

Option D: [tex]\((-9, 4)\)[/tex]

Substitute [tex]\(x = -9\)[/tex] and [tex]\(y = 4\)[/tex] into the equation:
[tex]\[ (-9-3)^2 + (4+4)^2 = 6^2 \][/tex]
[tex]\[ (-12)^2 + 8^2 = 36 \][/tex]
[tex]\[ 144 + 64 = 208 \neq 36 \][/tex]
So, [tex]\((-9, 4)\)[/tex] does not lie on the circle.

Option E: [tex]\((-3, -4)\)[/tex]

Substitute [tex]\(x = -3\)[/tex] and [tex]\(y = -4\)[/tex] into the equation:
[tex]\[ (-3-3)^2 + (-4+4)^2 = 6^2 \][/tex]
[tex]\[ (-6)^2 + 0^2 = 36 \][/tex]
[tex]\[ 36 + 0 = 36 \][/tex]
So, [tex]\((-3, -4)\)[/tex] does lie on the circle.

Thus, the point [tex]\((-3, -4)\)[/tex] is the correct answer. Therefore, the correct option is:

E. [tex]\((-3, -4)\)[/tex]